The impact of production of palm oil towards economic growth in Malaysia / Noor Juliana Abdullah Sani (Faculty of Business and Management, 2007)
This research report aims to identify the impact of production of palm oil towards economic growth in Malaysia. The increasing demand of production of palm oil has contributing to the economic growth in Malaysia. However, production of palm oil in Malaysia has to compete with Indonesia and production of soybeans oil that are capable in producing more products. Thus, factors that most influence the economic growth in Malaysia need to be identified. The objectives of this study are to study the production of palm oil in Malaysia, to study the production of soybean oil in Malaysia and to determine whether capital or labor is the most factors influence the economic growth in Malaysia. The study used descriptive research design. It focused on the production of palm oil in Malaysia scope. It involved the selection and analysis of secondary data, journals and related write-up that are relating to production of palm oil in Malaysia that includes the factors that affecting production of palm oil, production of soybeans oil, capital and labor of production of palm oil. From the analysis of production of palm oil it can be seen that the total production is increasing year by year. There are constant increase in the production of palm oil and thus concluded that there is positive growth in the palm oil industry and the production of soybean is one factors that have contributed to the increasing the economic growth in Malaysia. On the other hand, the regression analysis clearly shows that the production of palm oil has positive relationship with the economic growth in Malaysia, and also positive relationship between production of soybeans oil, capital and labor of production of palm oil. Among all the factors. Production of palm oil and capital of production of palm oil has been identified as the factors that contribute the most economic growth in Malaysia.